Energy consumption and cost of seedbed preparation for lowland rice cultivation in Malaysia - Wan Ishak, Wan Ismail; Bochari-Gevao, S. M.; Yahya, Azmi; Teh, Christopher Boon Sung; Chan, Chee Wan (2005)
Seedbed preparation for lowland rice cultivation consumes considerable amount of energy. To reduce the energy expenditure for seedbed preparation, tillage treatment combinations of tractor forward speeds achieved with four transmission gear selection (Gear 1 High, Gear 2 Low, Gear 3 Low and Gear 4 Low) and three rotary tilling speeds (140 rpm, 175 rpm and 200 rpm) were studied. The cost of seedbed preparation was computed and benefits of the tillage treatment over control (Gear 3 Low and rotary tilling speed of 140 rpm) compared. Almost for every treatment, except Gear 2 Low and rotary tilling speed of 200 rpm, the energy input was lower than the control, making an energy saving to an extent of 0.5% to 33.8% and time saving of 3.3% to 35.4%. the cost of seedbed preparation was observed to linearly increase with increase in the total time spend for seedbed preparation. The minimum cost was for Gear 1 High and rotary tilling speed of 175 rpm and maximum cost was for the control. The benefit was maximum for Gear 1 High and rotary tilling speed of 175 rpm and minimum for Gear 2 Low and rotary tilling speed of 175 rpm. The result of the study suggest the adoption of Gear 1High and rotary tilling speed of 175 rpm for seedbed preparation under lowland rice cultivation.